A conserved core element is functionally important for maize mitochondrial promoter activity in vitro. - Caoile, A G (1997)
We have previously used a homologous in vitro transcription system to define functional elements of the maize mitochondrial atpA promoter. These elements comprise a central domain extending from -7 to +5, relative to the transcription start site, and an upstream domain of 1-3 bp that is purine rich and centered around positions -11 to -12. Within the central domain lies an essential 5 bp core element. These elements are conserved in many mitochondrial promoters, but their functionality has only been tested for atpA. In this study we have introduced mutations into the corresponding elements of two cox3 promoters and show that while the core element is essential for cox3 promoter activity, upstream element mutations have little or no effect. To define the minimal sequence required for in vitro promoter activity a series of short cloned oligonucleotides corresponding to the atpA promoter was used. While some activity was seen with a 14 bp sequence, full activity required 26 bp, suggesting that elements other than the core and upstream region can influence promoter strength. Another series of clones showed that altered spacing between the upstream and core elements of atpA had a significant effect on promoter activity. These results further define important features of the plant mitochondrial transcriptional machinery.